Early Modern Publishers : Identities and Strategies in the Book Trade - Cullen, Barnaby,; Maclean, Ian,; Weduwen, Arthur der, (Early Modern History and Modern History E-Books Online, Collection 2025, 2025)
Publishers play an indisputably important part in book history, but cover such wide areas of activity that they are rarely given a formal definition. This volume seeks to place the publisher at the heart of the early modern book trade. It examines their identities and careers, the business strategies they adopted for survival, their involvement in the professional, religious, political, and economic conditions in which they found themselves, and the constraints under which they had to operate. By presenting more than twenty case studies on individual and groups of publishers active in Sweden, Prussia, Switzerland, France, Italy, England, Ireland, Germany and the Low Countries, this volume makes a major contribution to the study of an elusive but essential figure in the history of the early modern book.